2017
DOI: 10.1166/jnn.2017.13078
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Different Shapes ZnFe2O4–BiOCl Nanocomposites for Photocatalytic Reduction of CO2 in Cyclohexanol

Abstract: Nanosheet and hierarchical microsphere nanostructures of ZnFe₂O₄–BiOCl nanocomposites with various ZnFe₂O₄ contents were prepared through hydrothermal deposition method. The morphology and structure of the as-prepared samples were systematically characterized by field emission scanning electron microscopy, transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, UV-vis diffuse reflectance spectroscopy, Brunauer-Emmert-Teller method, and photoluminescence spectra. The photocatalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Esterification between these two intermediates would form cyclohexyl formate, while part of the alcohol would be further oxidized to the ketone (Figure 14). This research group has also reported the combination of the zinc ferrite with bismuth oxychloride, BiOCl, for the same reaction [181,182]. Apparently, the same type of heterojunction as in the case of the ZnFe2O4/TiO2 can be formed with the oxychloride instead of titania, leading to improved photocatalytic activity with respect to the separate semiconductors.…”
Section: Ferrite-based Heterojunction Photocatalystsmentioning
confidence: 87%
See 2 more Smart Citations
“…Esterification between these two intermediates would form cyclohexyl formate, while part of the alcohol would be further oxidized to the ketone (Figure 14). This research group has also reported the combination of the zinc ferrite with bismuth oxychloride, BiOCl, for the same reaction [181,182]. Apparently, the same type of heterojunction as in the case of the ZnFe2O4/TiO2 can be formed with the oxychloride instead of titania, leading to improved photocatalytic activity with respect to the separate semiconductors.…”
Section: Ferrite-based Heterojunction Photocatalystsmentioning
confidence: 87%
“…In addition, systems with hierarchical microsphere microstructure showed higher photocatalytic activities, apparently due to a better charge carrier separation, than those with non-hierarchical nanosheet morphology [182]. Furthermore, photocatalytic activity in the ZnFe2O4/BiOCl system is also influenced by the exposed facets of BiOCl.…”
Section: Ferrite-based Heterojunction Photocatalystsmentioning
confidence: 93%
See 1 more Smart Citation